River Depth Analysis Using Multibeam Echosounder for Coal Ship Cruise Line (Case Study: Mahakam River, East Kalimantan) - Islami, Ahmad Ayyash; Yuwono, Yuwono; Handoko, Eko Yuli (IPTEK Journal of Proceedings Series, 2019)
Kalimantan is one of the largest coal producing regions in Indonesia. With abundant mining products, mining companies in Kalimantan need transportation media that can cover most of the mining areas. Water transportation is the answer that mining company need to transport mining products such a coal product. The Mahakam River is the main water transportation medium used to connect areas that can not be traversed by land in Kalimantan. In order to get safe transportation a cruise line must be developed. The cruise line is made from bathymetry survey using Multibeam Echosounder. The purpose of this study is to provide a safe cruise line for ships to pass the Mahakam River. A path will be made from bathymetry data and built from two specification. First specification is indonesian standard from kramadibrata and second is from ship specification itself. The data used for this research is from PT. Seascape Surveys Indonesia. Because the bathymetry data is the property of PT.Seascape Surveys Indonesia, the coordinates of this research area can not be mentioned and local coordinates are used to maintain the confidentiality of the company's data. Bathymetric data were corrected with survey error parameters consisting  of  tidal correction  correction, sound velocity profiler, gradient, water level and patch test. The depth of bathymetry data has reference to EGM96 during data retrieval and LLWL with reference EGM08 for Map. From the analysis of bathymetry maps of the Mahakam River, there will be recommendation which ship can pass the mahakam river and which ship is can’t.